(untitled) (Al-Academy, 2024)
Cinema is considered an art and creativity, in addition to being an industry in its own right. It is formed thanks to techniques that contribute to the creation of reality and imagination, to employing another form of logical perceptions when they have a direct presence, in addition to the possibility of this art to form public opinion about the phenomena surrounding us and how to deal with them, as well as building bridges. Communication between art and society. Cinema has also proven throughout its stages of development that it is capable of creating positive mental images by communicating with developments in technology. Accordingly, the researcher defined the title of his research: “The Artistic Style and Methods of Using Technology in the Feature Film” and presented it in four chapters. The first is the methodological framework, including the problem? What are the requirements for using technology in making a feature film? The importance of the research lies in the diversity of the use of the artistic style as a process of organizing the methods of using technology that accompanied the making of the narrative film. One of the objectives of the research is to reveal the processes of organizing the methods of technological diversity in creating forms and models in the narrative film, and the terms that were diagnosed in the keywords, and the second chapter, the theoretical framework, was prepared in three. The first topics are the artistic style as a marking system in the feature film, the second is methods for using the artistic style in the feature film, the third is the methods of using technology in the feature film, the third chapter is the research tool, the researcher followed the descriptive and analytical method, and the fourth chapter is the results and conclusions, among which technology contributes to expanding the circle of searching for new things. In the field of techniques to improve the quality of narrative films, the quality of production in narrative films is controlled by the channels of communication and communication, including technological techniques, and their dealings with the elements of cinematic language in their narrative and artistic context in continuous harmony to achieve the goal and means of how to make narrative films.